ANALISIS SEMIOTIKA KARAKTER ANIMASI NUSSA DAN RARRA SEASON 3 EPISODE ‘TOLONG DAN TERIMA KASIH’ - Zebrinna Delivia Putri Bahri; Clara Oktavia Firdaus (Peneliti.net, 2023)
The animated series of Nussa and Rarra is an animation allocated to children. This series explores Islamic values and character-building through storytelling animations. The complex problems are simplified with a light plot twist so that children can easily understand what they want to say through animation. The method used in this analysis was qualitative descriptive, with a semiotic approach. Barthes semiotic theory was used to analyze the character in the episode ‘Help and Thank You’ and then perfected by the Saussure and Pierce theory. This animation was chosen for analysis because it has a unique way of approaching audiens. This analysis intended to describe the character by seeing the visual of Nussa and Rarra animation at ‘Please and Thank You’ episode.